Surgical wound closure by staples or sutures?: Systematic review. Issue 25 (19th June 2020) - Cochetti, Giovanni; Abraha, Iosief; Randolph, Justus; Montedori, Alessandro; Boni, Andrea; Arezzo, Alberto; Mazza, Elena; Rossi De Vermandois, Jacopo Adolfo; Cirocchi, Roberto; Mearini, Ettore
Abstract: Aim: To compare the effects of sutures and staples for skin closure of surgical wounds. Material and methods: We included published and unpublished randomized controlled trials (RCTs) and cluster-randomized trials comparing staples with sutures. Patients were adults (aged 18 years or over) who had undergone any type of surgery. The primary outcomes were risk of overall and severe wound infection. Secondary outcomes included length of hospital stay, readmission rate, adverse events, patient satisfaction with cosmetic results, postoperative pain. Results: Forty-two very low to low quality RCTs with a total of 11, 067 patients were included. Sutures resulted in slightly fewer overall wound infections (4.90%) compared to staples (6.75%) but it is uncertain whether there is a difference between the groups (risk ratio [RR] 1.20, 95% confidence intervals [CI] 0.80–1.79; patients = 9864; studies = 34; I 2  = 70%). The evidence was also insufficient to state a difference in terms of severe wound infection (staples 1.4% vs sutures 1.3%; RR 1.08, 95% CI 0.61–1.89; patients = 3036; studies = 17; I 2  = 0%), grade of satisfaction (RR 0.99, 95% CI 0.91–1.07; patients = 3243; studies = 14; I 2  = 67%) and hospital stay. Staples may increase the risk of adverse events (7.3% for staples vs 3.5% for sutures; RR 2.00, 95% CI 1.44–2.79; patients = 6246; studies = 21; I 2  = 33%), readmission rate (RR 1.28, 95% CI 0.18–9.05; patients = 2466; studies = 5; I 2  = 66%) and postoperative pain (standardized mean difference [SMD] 0.41, 95%CI −0.35 to 1.16; I 2  = 88%, patients = 390 patients, studies = 5). Conclusions: Due to the lack of high quality evidence, we could not state if sutures are better than staples in terms of wound infection, readmission rate, adverse events, and postoperative pain. With a low quality of evidence, sutures reduce postoperative pain and improve grade of satisfaction with the cosmetic outcome. Abstract : Supplemental Digital Content is available in the text